Civil War canon : sites of Confederate memory in South Carolina - Brown, Thomas J., 1960- (Civil War America, 2015)
In this history of South Carolina's commemoration of the Civil War era, Thomas Brown uses the lens of place to examine the ways that landmarks of Confederate memory have helped white southerners negotiate their shifting political, social, and economic positions. By looking at prominent sites such as Fort Sumter, Charleston's Magnolia Cemetery, and the South Carolina statehouse, Brown reveals a dynamic pattern of contestation and change.